MOTIVATIONAL EDUCATION IN THE BOOK SHALÂH AL-UMMAH FÎ ‘ULUWW AL-HIMMAH BY SAYYID AL-‘AFFÂNÎ AND ITS EDUCATIONAL IMPLEMENTATION IN ISLAMIC UNIVERSITY - Rahendra Maya; Apud Saputra; Muhammad Fadilah Alfarisi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
As creatures that have more complex life needs, human are required to have the motivation to fulfill them and also to achieve various other life goals, even with high motivation. Especially in facing the 4.0 industrial revolution and to become a 5.0 society that is superior and competitive in all aspects of life, including in the aspect of education, even in Islamic education. The urgency of motivation and the need to be highly motivated is highly recommended in Islam, especially based on the Al-Qur’an and Al-Hadits as well as the opinions of the scholars and their implementation in various aspects of life. The reality of das sollen and das sein, is narrated explicitly and in detail by Sayyid Al-‘Affânî about the obligation of muslim to have high motivation as outlined in 15 volumes of his work entitled Shalâh Al-Ummah fî ‘Uluww Al-Himmah. Therefore, this research articles that use qualitative methods with a literature review and field study approach as well as data collection through descriptive documentation studies, observation, and field interviews to be analyzed qualitative-interpretatively. This article is intended to reveal Sayyid Al-‘Affânî thought about the urgency of motivation and objectivity and about the implementation of highly motivated education in Islamic university, especially from the managers and lecturers as well as the student.